Preservation of Yasinan and Marhabanan Traditions as a Form of Religious Moderation in KKN Activities: Notes on Community Service in Tegalgirang Village, Bangodua District, Indramayu Regency - Zahra, Fatimatuz (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
The tradition of Tahlilan, Yasinan, and Marhabanan held on Friday night in Tegalgirang Village is a form of integration between Islamic teachings and local culture. These activities not only function as a means of worship, but also have important social and cultural values. The resulting virtues include: (1) strengthening friendship between residents through social interaction in the mushalla, (2) implementing the value of alms with the tradition of food banquets, and (3) prospering the mushalla as a center of culture and community education. This tradition is an effective medium in maintaining environmental harmony and strengthening Islamic noble values in the community.